Painful Fibrous Nonunion of a Posterior Oblique Ligament Bony Avulsion Fracture Associated With Anterior Cruciate Ligament Tear: A Case Report. Issue 4 (15th October 2022) - Smith, John-Rudolph H.; Dittman, Lauren E.; Camp, Christopher L.; Levy, Bruce A.
Abstract : Case: This report describes a case of a posterior oblique ligament (POL) bony avulsion fracture associated with an anterior cruciate ligament (ACL) tear in a 16-year-old female gymnast. The avulsion fracture was discovered on repeat radiographs and magnetic resonance imaging after the patient developed increased pain after ACL reconstruction. After excising the bony avulsion and repairing the POL, she reported complete resolution of her preoperative pain. Conclusion: Bony avulsion fractures of the POL are rare and challenging to diagnose. Awareness of this injury and the subtle imaging findings will help clinicians appropriately diagnose and treat these lesions.